Analisis Penggunaan Aplikasi Catatan Kinerja Pegawai (ASLI CAKEP) dalam Sistem Informasi Penilaian Kinerja Pegawai di Balai Arsip Statis dan Tsunami Aceh - Ajirni; Akbar, Rizaldi; Hajrianti, Rahmi (Jurnal Sistem Komputer (SISKOM), 2023)
This research aims to analyze the use of the Employee Performance Record Application (ASLI CAKEP) in the Employee Performance Assessment Information System at the Aceh Static and Tsunami Archives Center. Research was conducted to provide an in-depth understanding of the effectiveness of using this application in the employee performance appraisal process, as well as the factors that influence its effectiveness. Research methods include data collection through interviews and observation, with analysis using qualitative analysis techniques. The research results show that the use of ASLI CAKEP is effective in increasing the efficiency of the assessment process, reducing subjectivity bias, and providing more structured feedback to employees. This application also helps in making it easier to access employee performance data, as well as supporting more informational managerial decision making. However, research has also identified several drawbacks in the use of these applications. Based on the results of the analysis, it is recommended to provide intensive training to users, carry out routine monitoring and evaluation, and be involved in developing application features and functionality to increase the effectiveness of its use.